Can mutual funds time risk factors? - Benos, E. (2015)
Using daily observations from 448 actively managed funds, we employ the methodology in Bollen and Busse (2001) in order to assess the ability of fund managers to time systematic risk factors. We first construct synthetic portfolios in order to obtain the empirical distribution of timing coefficients under the null hypothesis of no timing ability and then compare this distribution to that of the timing coefficients of the actual funds. Fund managers do not seem to be timing any of the risk factors. We interpret this result as evidence that factor timing ability does not persist over long time periods. © 2010 The Board of Trustees of the University of Illinois.